Seroprevalence and Sources of Toxoplasmosis among Orang Asli (Indigenous) Communities in Peninsular Malaysia - Romano, Ngui; Yvonne Ai, Lian Lim; Noor Farah Hani, Amir; Veeranoot, Nissapatorn; Rohela, Mahmud (The American Society of Tropical Medicine and Hygiene, 2011)
This study aims to evaluate the current seroprevalence of toxoplasmosis among indigenous communities in Peninsular Malaysia and relate its association with epidemiological data. Overall seroprevalence of Toxoplasma gondii was 37.0% with 31.0% immunoglobulin (Ig) G, 1.8% IgM, and 4.2% seropositivity for both anti- Toxoplasma antibodies. Multivariate analysis showed that age above 12 years (odds ratio [OR] = 2.70, 95% confidence interval [CI] = 1.75–4.04, P < 0.001), using untreated river and mountain water supplies (OR = 1.50, 95% CI = 1.01–2.40, P = 0.050), and close proximity with cats (OR = 1.40, 95% CI = 1.10–1.76, P = 0.010) were factors associated with toxoplasmosis. Given the high seroprevalence of toxoplasmosis among these communities who live in poor socioeconomic conditions, a comprehensive health surveillance program and screening should be initiated among women of childbearing age and pregnant women during the antenatal period for early diagnosis and treatment. The role of domestic cats and environmental contamination with oocyst in soil and water has to be highlighted and addressed in future prevention strategies for these communities.